2021
DOI: 10.1111/cdoe.12681
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic‐related inequality in dental care utilization among preschool children in China

Abstract: Objectives: This study aimed to investigate socioeconomic-related inequality in dental care service utilization in the past 12 months among Chinese preschool children and to explore the contribution of various factors to this inequality.Method: A total of 40 305 children aged 3-5 years from 372 kindergartens who participated in the Fourth National Oral Health Survey in China were included in the final analysis. The method of data weighting in complex sampling was adopted to make the samples more representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Earlier studies have revealed shortage in the dental workforce (common health care issue in rural areas) family income, socioeconomic status, mother's age, mother, parent or caregiver's education, dental visit, perception of child's oral health-related quality of life, child's age, dental pain, and dental caries experience, influenced child's dental visit. 7,10,11,[13][14][15][16]24,26 In this study child's factors such as their pain experience and decayed teeth and mother's education, perception on child's oral health-related quality of life and caries experience influence children's dental visit.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Earlier studies have revealed shortage in the dental workforce (common health care issue in rural areas) family income, socioeconomic status, mother's age, mother, parent or caregiver's education, dental visit, perception of child's oral health-related quality of life, child's age, dental pain, and dental caries experience, influenced child's dental visit. 7,10,11,[13][14][15][16]24,26 In this study child's factors such as their pain experience and decayed teeth and mother's education, perception on child's oral health-related quality of life and caries experience influence children's dental visit.…”
Section: Discussionmentioning
confidence: 97%
“…24 The male to female ratio were almost similar in the present study which is in line with previous studies. 7,[10][11][12][13][14][15][16]20,[24][25][26] Studies have reported either equal or varied (higher proportion of children from rural and urban) distribution of study participants. 14,15,25 In our study majority of the participants were recruited from urban location owing to the population dwelling in Bangalore urban district.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations